Contributions to the tribe Leptocorisini, with descriptions of Planusocoris schaeferi gen. & sp. nov. (Hemiptera: Alydidae) - Yi, Wenbo; Bu, Wenjun (Zootaxa, 2015)
In this paper, the genus Grypocephalus Hsiao, 1963 is taxonomically reviewed worldwide. Bloeteocoris Ahmad, 1965 is proposed as a new junior synonym for Grypocephalus Hsiao, 1963. All the species of Bloeteocoris Ahmad, 1965 are herein transferred to Grypocephalus Hsiao, 1963, in which, Bloeteocoris minutus Ahmad, 1965 is synonymized with Grypocephalus pallipectus Hsiao, 1963. Planusocoris schaeferi gen. & sp. nov. of Leptocorisini is described as new to science. Photographs of adults, and illustrations of male and female genitalia of the involved species are provided. The genera of the world Leptocorisini are keyed. The type specimens of P. schaeferi sp. nov. are deposited in the Insect Collection, Institute of Entomology, Nankai University, Tianjin, China.